Chronic hepatitis B surface antigen seroclearance‐related immune factors. Issue 1 (26th May 2016) - Yuan, Ting; Jiang, Yongfang; Li, Mei; Li, Wei
Abstract : The ultimate aims of the treatment of hepatitis B virus infection are the loss of hepatitis B surface antigen (HBsAg) andhepatitis B surface antibody seroconversion. Unfortunately, these goals are rarely reached. Many factors are associated with HBsAg seroconversion, including genetic, immune, and viral factors. However, the mechanism of HBsAg seroclearance, and particularly the immune mechanism, is still difficult to elucidate. The immune factor interferon‐α is currently the main antiviral therapy for chronic hepatitis B virus infection. However, a sustained shift from response of HBsAg to hepatitis B surface antibody seroconversion is rarely obtained. Recent studies have revealed that several of the newly identified immune factors are closely related to the removal of HBsAg. In this article, we review recent studies on these immune factors, their influence on hepatitis B progression, and HBsAg seroconversion.